cAMP promotes the differentiation of neural progenitor cells in vitro via modulation of voltage-gated calcium channels - Lepski, Guilherme; Jannes, Cinthia E.; Nikkhah, Guido; Bischofberger, Josef (Frontiers in Cellular Neuroscience, 2013)
The molecular mechanisms underlying the differentiation of neural progenitor cells (NPCs) remain poorly understood. In this study we investigated the role of Ca2+ and cAMP (cyclic adenosine monophosphate) in the differentiation of NPCs extracted from the subventricular zone of E14.5 rat embryos. Patch clamp recordings revealed that increasing cAMP-signaling with Forskolin or IBMX (3-isobutyl-1-methylxantine) significantly facilitated neuronal functional maturation. A continuous application of IBMX to the differentiation medium substantially increased the functional expression of voltage-gated Na+ and K+ channels, as well as neuronal firing frequency. Furthermore, we observed an increase in the frequency of spontaneous synaptic currents and in the amplitude of evoked glutamatergic and GABAergic synaptic currents. The most prominent acute effect of applying IBMX was an increase in L-type Ca2+currents. Conversely, blocking L-type channels strongly inhibited dendritic outgrowth and synapse formation even in the presence of IBMX, indicating that voltage-gated Ca2+ influx plays a major role in neuronal differentiation. Finally, we found that nifedipine completely blocks IBMX-induced CREB phosphorylation (cAMP-response-element-binding protein), indicating that the activity of this important transcription factor equally depends on both enhanced cAMP and voltage-gated Ca2+-signaling. Taken together, these data indicate that the up-regulation of voltage-gated L-type Ca2+-channels and early electrical excitability are critical steps in the cAMP-dependent differentiation of SVZ-derived NPCs into functional neurons. To our knowledge, this is the first demonstration of the acute effects of cAMP on voltage-gated Ca+2channels in NPC-derived developing neurons.